2015
DOI: 10.1097/mlr.0000000000000315
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30-Day Readmissions With Preadmission Electronic Health Record Data

Abstract: The PREADM is designed for use by health plans for early high-risk case identification, presenting discriminatory power better than or similar to that of previously reported models, most of which include data available only upon discharge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
106
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 106 publications
(118 citation statements)
references
References 39 publications
12
106
0
Order By: Relevance
“…40 Using regression trees and logistic models, it found that 11 variables, including chronic conditions, prior health services use, body mass index, and geographic location weakly predicted increased readmission risk (odds ratios Ͻ2.00). Those results differ from ours in that they did not indicate increased risk from polypharmacy and Charlson scores, and the study's 11-factor model was less predictive than our 2-item model.…”
Section: Discussionmentioning
confidence: 99%
“…40 Using regression trees and logistic models, it found that 11 variables, including chronic conditions, prior health services use, body mass index, and geographic location weakly predicted increased readmission risk (odds ratios Ͻ2.00). Those results differ from ours in that they did not indicate increased risk from polypharmacy and Charlson scores, and the study's 11-factor model was less predictive than our 2-item model.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, VE can distinguish planned care referrals to a limited set of subspecialists ( The multivariate analysis confirms many previous studies showing age, comorbidities, length of stay, and number of previous hospitalizations or ED visits are associated with increased odds of readmission. [35][36][37][38][39][40][41][42][43] Marital status, which may be a marker of social determinants of health, and gender have had variable associations with readmission. 41,42,47 In this study, neither gender nor marital status was associated with readmission odds.…”
Section: Discussionmentioning
confidence: 99%
“…For each measure of continuity, a multivariate analysis using logistic regression was conducted to adjust for known readmission risk factors. 1,[35][36][37][38][39][40][41][42][43] Odds ratios with 95% confidence intervals were calculated. Direct comparison of the 4 non-nested models over the entire dataset using Akaike's Information Criterion was not valid due to the fact that the UPC, COC, and SECON models all excluded different data due to their inherent division-by-zero problem.…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5] Research on characterizing revisit rates has many facets, ranging from the construction of risk indices 4,6 to examining statistical behavior 1,3,7-9 and constructing predictive models using machine learning principles. 10,11 Both 30 days 1,3,4,11 and 72 hours 7,8,10 have been used as cutoff points for whether a visit before a given ED encounter is considered a revisit. Such studies often treat insurance type as a factor; as such, there is not much information on the specific behavior of the space of Medicaid patients.…”
Section: Introductionmentioning
confidence: 99%